ANALISIS IMPLEMENTASI MASYARAKAT MEDAN AMPLAS TERHADAP ANJURAN PEMERINTAH MENGHADAPI COVID-19 - Cahya Agitsna, Sisca Amini; Hanum, Farida; Hanum, Sastriani; Syahputra Sagala, Rizky Karina; Suhairi, Suhairi (Universitas Labuhanbatu, 2021)
The epidemic that is happening at this time has caused many activities to be postponed. The outbreak, known as COVID-19, has had a very significant negative or bad impact on the people of Indonesia. The negative impact is felt by the entire community and all agencies or institutions. The very big impact is on the economy. The economy in Indonesia has declined greatly due to the Covid-19 outbreak. Meanwhile, the government continues to make recommendations or recommendations to the public regarding the existence of this covid-19, to avoid the increasing spread due to this covid-19. This epidemic is not only happening in Indonesia, but also throughout the world. So that the government is getting stricter and giving more recommendations to the public to stay alert and follow the advice of the government, so that efforts to eliminate COVID-19 can be carried out quickly for the sake of mutual comfort and prosperity.